OPTIMALISASI KEBUTUHAN MURID DAN HASIL BELAJAR DENGAN PEMBELAJARAN BERDIFERENSIASI - Wiwin Herwina (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
Abstract: Differentiated learning is an attempt to adjust the learning process in the classroom to meet the individual learning needs of each student. Differentiated learning is an adjustment to interests, learning profiles, and student readiness in order to achieve increased learning outcomes. Through differentiated learning activities, all their needs are accommodated according to their interests or learning profiles. In classes that apply differentiation learning, teachers must think that students have diverse learning needs and differ from one another. There are four (4) components of differentiated learning, namely: content, process, product, and learning environment. Differentiated learning is able to help students achieve optimal learning outcomes, because the products they will produce are according to their interests. Differentiated learning process must provide ample space for students to demonstrate what they have learned. Products produced by students can be presented in an article, song, poem, infographic, poster, video performance, video animation or other forms according to the skills and interests of each group.